2013
DOI: 10.1002/ldr.2206
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐Temporal Patterns of Land Use/Cover Changes Over the Past 20 Years in the Middle Reaches of the Tarim River, Xinjiang, China

Abstract: The interaction between land use/cover change and landscape pattern is pivotal in research concerning global environmental change. This study uses three different Landsat images of 1989, 1998 and 2009 to study the land use/cover and landscape pattern changes in the middle reaches of the Tarim River basin. envi®, erdas®, ArcGIS® and fragstats® software were used to analyse the land use/cover changes. The objectives of study were to map and study the changes in land use/cover and landscape pattern, and propose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Th t F2 classes' ar isted in 1986-2 of Fragile (F2) e of reduction easing Table 7 The change of e ion of ty of ation in Dhaka of Bangladesh reported that many constructions were carried out in the study period, as well as a significant decrease in the amount of water, arable land and vegetation cover due to increased urbanization, population growth and economic development. In this study also, forest and rangeland degradation reduced, change and conversion of these land uses area into other land uses are evident that is consistent with the results of Parabaharan et al (2010) and Zhang et al (2015). The results showed that vegetation cover is dominant criterion in desertification of Maraveh Tappeh.…”
Section: Analyzsupporting
confidence: 92%
“…Th t F2 classes' ar isted in 1986-2 of Fragile (F2) e of reduction easing Table 7 The change of e ion of ty of ation in Dhaka of Bangladesh reported that many constructions were carried out in the study period, as well as a significant decrease in the amount of water, arable land and vegetation cover due to increased urbanization, population growth and economic development. In this study also, forest and rangeland degradation reduced, change and conversion of these land uses area into other land uses are evident that is consistent with the results of Parabaharan et al (2010) and Zhang et al (2015). The results showed that vegetation cover is dominant criterion in desertification of Maraveh Tappeh.…”
Section: Analyzsupporting
confidence: 92%
“…In comparison with various novel classifiers, the traditional maximum likelihood classifier has generally been used because of its ease in application, simple operation and good performance [28]. In this study, a supervised classification based on the maximum likelihood classification (MLC) method was employed to classify the individual images independently.…”
Section: Lclu Classification Methodsmentioning
confidence: 99%
“…In this way, the offset can be estimated in every direction. The shifting distances and the shifting angles from the lake's previous centroid to the next are calculated by identifying the quadrant in which the deflection occurs [38,39]. All of the distance values in each quadrant in each time period are accumulated, and values in the opposite direction (such as north and south) cancel out.…”
Section: Centroid Determination Analysismentioning
confidence: 99%